CNVs and clinical diagnosis - Levy, Brynn (Henry Stewart Talks, 2009)
Genetic and chromosomal imbalance, Survivable and "viable" chromosomal imbalance, Clinical implications of chromosome abnormalities, Chromosome analysis, Diagnostic limits of conventional cytogenetic analysis, How does banding resolution impact diagnostic ability?, Molecular cytogenetics, Fluorescence in situ hybridization (FISH), The clinical phenotype guides the choice of FISH test, How do we determine the origin of marker chromosomes?, Trisomy rescue, Microarray analysis in clinical genetics, Probe spacing and resolution, Single nucleotide polymorphism oligonucleotide microarray analysis (SOMA) in clinical cytogenetics, Partial aneuploidy, Ring chromosome, Gene composition of duplicated region, Subtelomeric imbalances, Gene composition of delete region, FISH using Di George probe, Neurofibromatosis, Duchenne muscular dystrophy, Rubinstein-Taybi syndrome, Uniparental disomy, Benefits of microarray analysis in clinical genetics